2016
DOI: 10.1016/j.kint.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1 plays a role in phosphate-induced vascular smooth muscle cell calcification

Abstract: Medial vascular calcification is a common complication of chronic kidney disease (CKD). Although elevated inorganic phosphate stimulates vascular smooth muscle cell (VSMC) osteogenic transdifferentiation and calcification, the mechanisms involved in their calcification during CKD are not fully defined. Because hypoxic gene activation is linked to CKD and stimulates bone cell osteogenic differentiation, we used in vivo and in vitro rodent models to define the role of hypoxic signaling during elevated inorganic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(126 citation statements)
references
References 71 publications
6
116
2
2
Order By: Relevance
“…A recent study in animal models investigated the role of hypoxia and HIF‐1 signaling in the development of vascular calcifications. The study suggested that HIF‐PHIs might enhance phosphate‐induced vascular smooth muscle cell calcification in CKD or ESRD patients with poorly controlled mineral bone metabolism . A molecular link also exists between HIF and FGF23 signaling, which may negatively impact cardiovascular risk in HIF‐PHI‐treated CKD patients .…”
Section: Hif‐prolyl Hydroxylases As Drug Targets In Renal Anemiamentioning
confidence: 98%
“…A recent study in animal models investigated the role of hypoxia and HIF‐1 signaling in the development of vascular calcifications. The study suggested that HIF‐PHIs might enhance phosphate‐induced vascular smooth muscle cell calcification in CKD or ESRD patients with poorly controlled mineral bone metabolism . A molecular link also exists between HIF and FGF23 signaling, which may negatively impact cardiovascular risk in HIF‐PHI‐treated CKD patients .…”
Section: Hif‐prolyl Hydroxylases As Drug Targets In Renal Anemiamentioning
confidence: 98%
“…HIF-1 has been reported to play a crucial role in vascular smooth muscle cell (VSMC) calcification [127]. During the progression of CKD, VSMC calcification and osteogenic trans-differentiation are significantly promoted by hypoxic condition.…”
Section: Hif In Ckd-associated Syndromesmentioning
confidence: 99%
“…Meanwhile, HIF-1 activators can further promote inorganic phosphate induced calcification. Together, hypoxia can synergize with elevated inorganic phosphate through HIF-1 induction to enhance VSMC osteogenic transdifferentiation [127]. Furthermore, Bone Gla Protein (BGP), a marker for bone formation which is induced in calcified vasculatures, may also promote HIF-1α expression and further stimulate the calcification [128].…”
Section: Hif In Ckd-associated Syndromesmentioning
confidence: 99%
“…Phosphate loading induces the expression of hypoxia‐inducible factor‐1α (HIF‐1α) in smooth muscle cells (SMCs) . This transcription factor is reported to be responsible for the calcification of SMCs by phosphate loading.…”
Section: Potential Solutions For Vascular Calcification In the Futurementioning
confidence: 99%